Determinants of Customer Satisfaction and eWOM in the Sharing Economy: Timeshare versus Peer-to-Peer Accommodations - Jennifer Redditt; Marissa Orlowski; Alan Fyall; Amy M. Gregory; Heejung Ro (Tourism and Hospitality, 2022)
This study aims to investigate the differential effects of determinants of satisfaction on subsequent electronic word-of-mouth (eWOM) behavior in the sharing economy with peer-to-peer accommodations and timeshares. Data were collected from consumers who stayed at either a timeshare or peer-to-peer accommodation within the previous year (N = 785). Structural equation modeling was used to test the relationship between the determinants and eWOM through satisfaction, followed by multiple-group comparison to examine the moderating effect of accommodation type. The results indicated that amenities, economic benefits, and trust demonstrated an indirect effect on eWOM behavior through satisfaction, but community belonging affected eWOM behavior directly. Multiple-group SEM revealed that accommodation type moderated the indirect effects of community belonging, economic benefits, and trust on eWOM behavior, such that the indirect effect was significant only for timeshare accommodations. This study contributes to the sharing economy literature by filling the gap of lodging research beyond Airbnb and including timeshares. The findings highlight competitive differences that influence eWOM between peer-to-peer accommodations and timeshares that otherwise offer similar home-like accommodations. The study revealed a newly found direct relationship between community belonging and eWOM.